Association of Strong Smoke-Free Laws With Dentists’ Advice to Quit Smoking, 2006–2007 - Gonzalez, Mariaelena (American Public Health Association, 2014)
Objectives. We examined the association of smoke-free laws with dentists’ advice to quit smoking and referral to a quit line, among smokers who reported visiting the dentist in the past 12 months. Methods. We used the 2006 to 2007 Tobacco Use Supplement of the Current Population Survey merged with the American Nonsmokers' Rights Foundation Local Ordinance Database of smoke-free laws. The dependent variables were advice from a dentist to quit smoking and referral to a quit line, and the independent variable of interest was 100% smoke-free law coverage. We controlled for respondent demographics and an index of state-level smoking ban attitudes (included to ensure that the effect detected was not the result of social attitudes). Results. Smoke-free law coverage was associated with dental advice to quit smoking (odds ratio [OR] = 1.27; 95% confidence interval [CI] = 1.01, 1.59; P = .041), but not with referral to a quit line (OR = 1.33; 95% CI = 0.79, 2.25; P = .283). Conclusions. Interventions with dentists are needed to increase referrals to quit lines and other smoking cessation efforts.